A study of the biology of the Jameson reservoir near Grahamstown, Cape Province - Darbyshire, John Frederick (Rhodes University, Faculty of Science, Botany Department, 1959)
1. This thesis is an ecological study of a South African water storage reservoir and it's tributary streams. 2. A brief description of the reservoir, the surrounding vegetation, superficial geological strata, soils and early history of the reservoir is given in Chapter I. 3. The surrounding vegetation is discussed in some detail in Chapter II. The zonation of the plants and the influence of water upon it are discussed. 4. The results of the regular investigations of the physicochemical environment are presented in Appendix 1 and the salient points noted in Chapter III. 5. The species of algae collected are listed in Appendix 2 and in Chapter IV are discussed in relation to habitat and abundance. 6. The animals are dealt with in a similar manner in Chapter V. Under 'Discussion and Conclusions' in Chapter VI an attempt is made to review the findings and discuss their significance.
Keywords: Uncatalogued